2018
DOI: 10.4028/www.scientific.net/kem.762.288
|View full text |Cite
|
Sign up to set email alerts
|

Phase Composition and Morphology of Tungsten Oxide Nanoparticles Produced via a Pyrolytic Process

Abstract: The chemical synthesis is a leading route for the purposeful design of nanomaterials, whereas the tungsten oxides are employed in a variety of special applications. The production of nanomaterials by traditional synthetic methods is still a cumbersome multistep procedure. Here we propose an improved method to produce tungsten oxide nanoparticles via a pyrolytic process. A tungsten-containing precursor was prepared by liquid extraction using n-trioctylamine (C8H17)3N solution in toluene. We have shown that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The method does not require high-temperature treatment, toxic reactants, complex operations, or special equipment. Using EPM, various oxide materials are produced, including nanocrystalline powders of cobalt Co 3 O 4 , tungsten WO 3 , gadolinium Gd 2 O 3 and magnesium MgO oxides [ 30 , 31 , 32 , 33 ], supported catalysts [ 34 ], and magnetic materials, such as FePt and Fe 3 O 4 /Pt [ 35 , 36 ]. The performed investigations showed that this synthesis method is fast, scalable, and well reproducible, providing a promising avenue for industrial applications of novel magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The method does not require high-temperature treatment, toxic reactants, complex operations, or special equipment. Using EPM, various oxide materials are produced, including nanocrystalline powders of cobalt Co 3 O 4 , tungsten WO 3 , gadolinium Gd 2 O 3 and magnesium MgO oxides [ 30 , 31 , 32 , 33 ], supported catalysts [ 34 ], and magnetic materials, such as FePt and Fe 3 O 4 /Pt [ 35 , 36 ]. The performed investigations showed that this synthesis method is fast, scalable, and well reproducible, providing a promising avenue for industrial applications of novel magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%